Die skedelmorfologie van Pelomedusa Galeata (Wagler) - Van der Merwe, N. J.(Nicolaas Johannes),1916-1969 (Stellenbosch : Stellenbosch University, 2012)
Verhandeling (M. Sc.) -- Universiteit van Stellenbosch, 1939.